If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8g+6(g-2)=-10(g-4)2g
We move all terms to the left:
8g+6(g-2)-(-10(g-4)2g)=0
We multiply parentheses
8g+6g-(-10(g-4)2g)-12=0
We calculate terms in parentheses: -(-10(g-4)2g), so:We add all the numbers together, and all the variables
-10(g-4)2g
We multiply parentheses
-20g^2+80g
Back to the equation:
-(-20g^2+80g)
-(-20g^2+80g)+14g-12=0
We get rid of parentheses
20g^2-80g+14g-12=0
We add all the numbers together, and all the variables
20g^2-66g-12=0
a = 20; b = -66; c = -12;
Δ = b2-4ac
Δ = -662-4·20·(-12)
Δ = 5316
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{5316}=\sqrt{4*1329}=\sqrt{4}*\sqrt{1329}=2\sqrt{1329}$$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-66)-2\sqrt{1329}}{2*20}=\frac{66-2\sqrt{1329}}{40} $$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-66)+2\sqrt{1329}}{2*20}=\frac{66+2\sqrt{1329}}{40} $
| 5=1–2u | | -4(1x+6)=-16 | | 6m2+24m=0 | | 5/12d+1/12d+1/6d+1/3d=6 | | 4(-3x+3)=-36 | | 24=y4+14 | | 3c+6=23 | | -14x=24x+38 | | -5(1x-7)=15 | | 16−2t=11/3t+9 | | 0=2n2-8n | | 1764/28=a | | -5x-2=-6-6x | | 2x2-26x=0 | | 3(4x+2)=20x+9+2 | | -19x-19=-19x-38 | | -5x-2=6-6x | | 7x2-x=0 | | 3(5x-3)-12x=10(2x-5)-10 | | (7x-19)=65 | | 11n2+10n=13 | | 4x+24=x+51 | | p-(p+4)=4(p-1)7/2p | | 4K-k-2k+5k=12 | | 44X0.06x=35X0.09x | | 2-3x=6x+5 | | 6x-12=10x+2 | | 32+25x=18 | | .5x+9=17 | | 44X0.06y=35X0.09y | | 2x+6=4x-5 | | -5x+16=7x=2(x=8) |